Influence of physical exercise on chemical lean body mass composition of rats submitted to food restriction (Revista Brasileira de Ciências Farmacêuticas, 2004)
The combination of a diet for body weight reduction with physical exercise (PE) can result in a smaller decrease in lean mass ((LM) compared to the use of a diet as the single strategy for weight loss. However, little is known about the influence of this combination on LM composition. On this basis, the objective of the present study was to determine the effect of PE on LM composition in rats submitted to food restriction (FR). Thirty-six Wistar rats (315 ± 15 g) were divided into the following 6 equal groups: sedentary with an ad libitum diet (S); trained, with an ad libitum diet (T); S, with 25% FR (FR25%); S, with 50% FR (FR50%); T, with FR25% (T + FR25%), and T with FR50% (T + FR50%). The experiment lasted six weeks and the training used was swimming with an overload of 5% of body weight, five sessions/week of 60 minutes each. The chemical composition of the carcass and the concentration of glycogen and protein in the gastrocnemius muscle of the animals were determined. The percentage of protein in the carcass and the concentration of protein in the gastrocnemius muscle were lower (p